KONTRIBUSI PAJAK HIBURAN DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) PADA DINAS PENDAPATAN KABUPATEN PAMEKASAN - Fajar, Achmarul (JURNAL AKUNTANSI DAN INVESTASI, 2017)
The government can collect entertainment taxes such as music performances, karaoke, billiard, water recreation, for those who entertain entertainment, the entertainment tax is one of the potential areas that are very important to be improved. To know the amount of contribution of entertainment tax to local income and the effectiveness of entertainment tax of Pamekasan Regency. This research take object at Office of Revenue Service, research type using quantitative descriptive method. This type of data in this research uses quantitative data, data source in the form of primary and secondary data. Data collection techniques in this study using the method of documentation and interviews. The analysis data used in this research is identifying target data and entertainment tax realization, identifying target data and realization of local revenue, calculating contribution of entertainment tax to local revenue, calculating the effectiveness of entertainment tax.Based on the research result, the contribution of entertainment tax to local revenue in 2011 amounted to 0.05%, in 2012 by 0.04%, in 2013 by 0.05%, in 2014 by 0.04%, and for the year 2015 By 0.05%. Average entertainment tax contribution of 0.05% from 2011 to 2015, this is classified under very less criteria. The effectiveness of entertainment tax revenue for 2011 amounted to 179.01%, in 2012 of 161.99%, in 2013 of 186.36%, in 2014 of 245.23%, and for 2015 by 152.59%. With an average rate of effectiveness of entertainment tax revenue of 185.04%, this includes very effective in Pamekasan District. Suggestions for pamekasan service to be more able to optimize the potential of entertainment tax which is in Pamekasan Regency.